ANALYSIS STUDY ON ENVIRONMENTAL AWARENESS AMONG STUDENTS - Das, Dola; Kashyap, Babhuti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to look at college students’ environmental awareness abilities in connection to their gender and degree of education. A purposive selection strategy was used to choose a sample of 60 college students who were evenly divided by gender and educational level. The sample was drawn from a number of colleges in Ahmadabad. Environmental Awareness Ability was measured using tools such as the Environmental Awareness Ability Measure (EAAM). The’t’ test was used to statistically assess the results. The data indicated that there was no substantial difference between them in terms of gender, and there was a negligible difference in terms of educational attainment. The natural atmosphere was so clean, virgin, unspoiled, uncontaminated, and welcoming to all living things.